Cambios socioculturales y consumo de las familias costarricenses - Barquero, Jorge (2016)
This article reflects on and analyses the family in general, viewed like social institution that mediates among macro and micro social dynamics. In other words, the general social change and actions of individuals converge in the household. The general historical context constitutes the socioeconomic, cultural and demographic changes that Costa Rica has experienced in the last three decades. These changes have influenced lifestyles and are expressed in different consumption patterns which are analyzed here according to the phases of the life cycle and the socioeconomic level of households. The general findings show how as families go through the different phases or stages of their life cycle, changes take place in their consumption patterns. Those consumption pattern changes analyzed by income levels reflect the growing socioeconomic inequalities that characterize the current Costa Rican society.